Clinical Implication of Corrective Saccades in the Video Head Impulse Test for the Diagnosis of Posterior Inferior Cerebellar Artery Infarction - Nam, Gi-Sung; Shin, Hyun-June; Kang, Jin-Ju; Lee, Na-Ri; Oh, Sun-Young (Frontiers in Neurology, 2021)
Objective: In the present study, we characterized the vestibulo-ocular reflex (VOR) gain and properties of corrective saccades (CS) in patients with posterior inferior cerebellar artery (PICA) stroke and determined the best parameter to differentiate PICA stroke from benign peripheral vestibular neuritis (VN). In particular, we studied CS amplitude and asymmetry in video head impulse tests (vHITs) to discriminate these two less-studied disease conditions. Methods: The vHITs were performed within 1 week from symptom onset in patients with PICA stroke (n = 17), patients with VN (n = 17), and healthy subjects (HS, n = 17). Results: PICA stroke patients had bilaterally reduced VOR gains in the horizontal semicircular canal (HC) and the posterior semicircular canal (PC) compared with HSs. When compared with VN patients, PICA stroke patients showed preserved gains in the HC and anterior semicircular canal (AC) bilaterally (i.e., symmetric VOR gain). Similar to VOR gain, smaller but bilaterally symmetric CS in the HC and AC were observed in PICA stroke patients compared with VN patients; the mean amplitude of CS for the ipsilesional HC was reduced (p < 0.001, Mann–Whitney U-test), but the mean amplitude of CS for the contralesional HC was increased (p < 0.03, Mann–Whitney U-test) in PICA stroke compared with VN. The receiver operating characteristic (ROC) curve showed that CS amplitude asymmetry (CSs) and VOR gain asymmetry (Gs) of HC are excellent parameters to distinguish PICA stroke from VN. Conclusion: In the current study, we quantitatively investigated the VOR gain and CS using vHITs for three semicircular canals in PICA stroke and VN patients. In addition to VOR gain, quantitative assessments of CS using vHITs can provide sensitive and objective parameters to distinguish between peripheral and central vestibulopathies.